A comprehensive NLP-based voice assistant system for streamlined information retrieval in metro rail services of Bangladesh - Rahman, MD. Abir; Alamgir, Adnan; Chowdhury, Shaheedul Haque; Mushtari, Maliha; Anzum, Wasim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.